Online learning communities in the New 'U'. (23rd July 2009) - Thoms, Brian; Garrett, Nathan; Ryan, Terry
In an academic world largely dominated by instructor-facilitated learning environments (i.e., lecture halls and course management software), our research implements and measures the impact of a student-owned and operated virtual learning environment. Adopting an Action Design research methodology, we look to expand scholarships and build communities within our graduate school setting. More specifically, our research explores the impact of a user-defined Online Learning Community (OLC) on a group of 118 graduate students across 6 doctoral courses. Our findings reflect positively on a number of constructs, including perceived learning, social interaction and community and have provided our university with a proof-of-concept OLC, offering a valid alternative to traditional Course Management Systems (CMS).